Spitzer Matching Survey of the UltraVISTA Ultra-deep Stripes (SMUVS): Full-mission IRAC Mosaics and Catalogs - Ashby, M. L. N.; Caputi, Karina I.; Cowley, Will; Deshmukh, Smaran; Dunlop, James S.; Milvang-Jensen, Bo; Fynbo, Johan P. U.; Muzzin, Adam; McCracken, H. J.; Fèvre, Olivier Le; Huang, Jia-Sheng; Zhang, J. (The Astrophysical journal. Supplement series, 2018)
This paper describes new deep 3.6 and 4.5 m imaging of three UltraVISTA near-infrared survey stripes within the COSMOS field. The observations were carried out with Spitzer's Infrared Array Camera (IRAC) for the Spitzer Matching Survey of the UltraVISTA Deep Stripes (SMUVS). In this work we present our data reduction techniques, and document the resulting mosaics, coverage maps, and catalogs in both IRAC passbands for the three easternmost UltraVISTA survey stripes, covering a combined area of about 0.66 deg2, of which 0.45 deg2 have at least 20 hr of integration time. SMUVS reaches point-source sensitivities of about 25.0 AB mag (0.13 Jy) at both 3.6 and 4.5 m, with a significance of 4 , accounting for both survey sensitivity and source confusion. To this limit the SMUVS catalogs contain a total of ∼350,000 sources, each of which is detected significantly in at least one IRAC band. Because of its uniform and high sensitivity, relatively large area coverage, and the wide array of ancillary data available in COSMOS, the SMUVS survey will be useful for a large number of cosmological investigations. We make all images and catalogs described herein publicly available via the Spitzer Science Center.